1987
DOI: 10.1177/875687058700800409
|View full text |Cite
|
Sign up to set email alerts
|

Gifted students in rural environments: Implications for school programs

Abstract: This article considers factors in rural environments that influence the achievement of the brightest students in such areas. It examines the educational needs of those rural students who are identified as gifted and explores some characteristics of rural families and communities that may contribute to the underachievement of gifted students in those communities. Implications for curriculum, instruction, and achievement are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 7 publications
0
19
0
2
Order By: Relevance
“…Additionally, the females in this study reported higher overall levels of anxiety than did males (see also Felson & Trudeau, 1991). This may have been due in part to the reluctance of males to admit anxiety (Wigfield & Eccles, 1989) or to the stereotypical science sex-role expectations that are believed to discourage high-achieving females (Howley, Pendarvis, & Howley, 1988).…”
Section: Gender Differences In Worry and Emotionalitymentioning
confidence: 72%
“…Additionally, the females in this study reported higher overall levels of anxiety than did males (see also Felson & Trudeau, 1991). This may have been due in part to the reluctance of males to admit anxiety (Wigfield & Eccles, 1989) or to the stereotypical science sex-role expectations that are believed to discourage high-achieving females (Howley, Pendarvis, & Howley, 1988).…”
Section: Gender Differences In Worry and Emotionalitymentioning
confidence: 72%
“…In addition, the CLEAR curriculum approach works to mitigate students’ feelings of marginalization and reduce factors obstructing students from reaching their full potential (Azano et al, 2017, p. 67). To minimize “social and economic” disadvantages of rural gifted students, Howley, Pendarvis, and Howley (1988) proposed acceleration as an efficacious means for challenging advanced students to reach their potential (p. 48). Acknowledging budget shortfalls in rural schools, Howley et al purported the cost effectiveness of using acceleration not only for students identified as gifted but “all students who are able” (p. 48).…”
Section: Curricula In Rural Gifted Educationmentioning
confidence: 99%
“…Prior research has suggested that rural adolescents must contend with a range of formidable challenges to their career development and preparedness to make post-high school transitions (e.g., Bores-Rangel, Church, Szendre, & Reeves, 1990;Howley, Pendarvis, & Howley, 1988;Lamb & Daniels, 1993;Lapan, Hinkelman, Adams, & Turner, 1999;Post-Kammer, 1985;Rojewski, 1995). For example, rural adolescents may have lower career aspirations and greater expectations for entering the workforce immediately after high school than do adolescents who live in other settings.…”
mentioning
confidence: 99%